Advancing tropical forestry curricula through non-timber forest products - Guariguata, Manuel R.; Evans, K. (2010)
There is growing consensus that the expanding scope of tropical forestry is not properly reflected in the way students are being trained. Forestry graduates across the tropics remain poorly equipped on how to engage with local stakeholders, on the technical and economic aspects of multiple-use management, on participatory approaches to forest resource use, and on how to respond effectively to global forestry paradigms. By their very nature, non-timber forest products (NTFPs) are located at the heart of a pluralistic view of tropical forest use and management and their inclusion in forestry curricula could promote interdisciplinary training. In this paper we provide some insights on the status and trends of NTFP education in Latin America through a synthesis of interviews with experts and the results of an electronic survey in order to outline some of the obstacles that need to be overcome in order to advance forestry curricula by using NTFPs. We argue that NTFPs are suitable to introduce topics that traditionally have not been taught to university level forestry students yet not necessarily through formal courses on NTFP management or textbooks on the topic. Instead, a modular approach may be a potentially effective way to promote interdisciplinary thinking and enhance adoption by university professors.